PRE-DESIGN OF INTEGRATED COCOA (THEOBREMA CACAO L.) POSTHARVEST SYSTEM WITH CONTROLLED FERMENTATION TECHNOLOGY IN DESA GENGGELANG, KABUPATEN LOMBOK UTARA, NUSA TENGGARA BARAT: IMPROVING QUALITY AND PRODUCTIVITY OF COCOA BEANS (THEOBREMA CACAO L.) WITH LARGE-SCALE CONTROLLED FERMENTER IN LOMBOK, NUSA TENGGARA BARAT - Ariasena, Diemas
Fermentation is important stage in the cocoa postharvest process to determine the quality of cocoa beans. Fermentation in Indonesia is generally carried out naturally or spontaneously without the addition of a starter and can be carried out using wooden box media. However, natural fermentation is constrained by changing environmental conditions that affect the consistency of the quality of fermented cocoa beans. The use of controlled fermenter can create a more consistent environment so that it is expected to improve the consistency of the quality of cocoa beans. The success of cocoa fermentation is determined by the dynamics and succession of the growth of key microbes that act as directors of the fermentation process such as lactic acid bacteria (LAB). Thus, the aim of this study was to determine the effect of using a controlled fermenter on improving the quality of cocoa beans. There are 3 types of treatment used in this study, namely: (1) natural fermenter (FA), controlled fermenter without the addition of inoculum (FT), (3) controlled fermenter with the addition of 10% lactic acid bacteria isolate (FT10). Fermentation conditions carried out were: cacao beans weighing ±20 kg, good quality beans (thick pulp, white color), initial pH ±3, the temperature in the controlled fermenter was maintained at 36-38oC, stirring was done once every 2 days in the natural fermenter and 1 once a day in a controlled fermenter, and all tests were carried out in duplicate. The results showed that the FT10 treatment was able to maintain the acidity (pH) of cocoa in the range of 4-6 during fermentation, and a temperature of 29-39oC during the fermentation process. With the highest total phenol content and number of beans per 100 grams was 100.9 mg GAE and bean quality was A (87.5 beans per 100 grams), the highest organoleptic analysis was on the bitterness indicator (3 .66), acidity (3.79) and color (3.58). In addition, the FT10 treatment can accelerate the fermentation time from 5 to 4 days so that the application of a controlled fermenter can not only maintain the quality of cocoa beans but also increase productivity. While the best IC50 value was found in the FA treatment with a value of 5.68 ppm.